The notarial eviction - Agurto Moreno, Jean Fredy (2020)
The author makes a brief analysis and comment on the Law n. 30933, specifying the purpose of the law and its scope, dealing with the notarial function in relation to non-contentious matters, analyzing the notary powers the non-contentious nature of the procedure originated by the Law, to later deal with its relationship with the eviction process institute. The active authority in this procedure, the lease agreement in accordance with the provisions of the Law, explaining the notarial procedure designed to establish the grounds for eviction and finally the aspects to be considered in relation to Law n. 30933, specifying their conclusions.